Investigation of NiO/CdO/Co3O4 ternary nanocomposite for sunlight-driven degradation via photocatalyst and antimicrobial studies - Mani Rajkumar; Rangaswamy Navamathavan (Next Materials)
In this study, co-precipitation method was used to successfully synthesize NiO/CdO/Co3O4 nanocomposite, which was subsequently characterised by using X-ray diffraction (XRD), was proven pure NiO, CdO and Co3O4. FTIR, FESEM with energy dispersive X-ray spectrometry (EDAX), and TEM. The XRD analysis demonstrated the presence of the NiO (cubic) CdO (cubic)– Co3O4 (hexagonal) structure, with an average crystallite size of NiO (25 nm), CdO (45 nm), and Co3O4 (33 nm). Also. the average particle size of 32.70 nm was identified in HRTEM morphology. The characteristic vibrational peaks at 607, 578, and 669 cm−1 of Ni–O, Cd–O, and Co–O were verified by FTIR. The agglomerated uniform shape is evident in the surface morphological images. The degradation of methylene blue (MB) dye in the presence of sunlight was used to test the samples' photocatalytic activity. It took 180 min for the ternary nanocomposite sample to reach the maximum degrading efficiency of 95 %. The kinetics and absorption capacity of the samples were also assessed. The absorption of photons in the visible region increased the generation of electron-hole pairs, leading to the production of reactive oxygen species (RO-species) responsible for photocatalytic activity. As a result, the NiO/CdO/Co3O4 exhibited distinctive photocatalytic activity under sunlight. The antibacterial activity was evaluated in vitro against Streptococcus mutans, Staphylococcus aureus (gram-positive), Klebsiella pneumonia, and Escherichia coli (gram-negative) at varying concentrations (150, 200, and 250 µg/mL). The antibacterial activity of the 16 mm zone of inhibition against Klebsiella pneumonia, a gram-negative bacterium, is significant.